NEW APPROACHES TO INCREASING THE EFFECTIVENESS OF VACCINATION WITH TYPHOID VACCINES IN MEDICINE AND SPORTS - Dilbar D. Safarova; Saida N. Sharipova (Western European Studies, 2026)
Typhoid fever, caused by a variety of bacteria, remains a serious public health problem, especially in regions with poor sanitation and limited access to clean water. One of the key strategies for the prevention of typhoid fever is the implementation of effective immunoprophylaxis measures. Vaccine prevention is recognized throughout the world as a decisive factor in reducing the incidence of infectious diseases, mitigating the severity of clinical symptoms and reducing mortality rates. About 343 people were examined in the work. All examined were males aged 18-22 years. To conduct the research, we used Vaccination with a chemical sorbed liquid typhoid vaccine produced by Uzbiopharm OJSC. Vaccination with dry alcoholic typhoid vaccine produced in the Russian Federation (series No. 23-2, K 23, R 94.161.387). Based on the results, it was concluded that the immunological effectiveness of the typhoid vaccine VBTHSJ OJSC "Uzbiofarm" was 66.66%, and the vaccine BTVSS RF - 74.58%. Immunomodulin contributed to an increase in the effectiveness of the VBTHSJ vaccine of Uzbiopharm OJSC from 66.66% to 95.17%
Keywords: immunological vaccine; typhoid vaccine; immunobiological